Anatomy of an innovation in IT service. Issue 1 (May 2018) - Ghoshal, Sankar; Roy, Rahul Kumar
The case study covers aspects of service innovation in the IT services sector. The client Nordics is a global telecommunication major. They have a large and diverse set of IT business applications, most of which is on SAP applications. The subject of the case study is that of SAP Releases, the service of enhancing and creating new business functionalities in the existing business applications. The case is seen from the perspective of the Program Manager of the SAP Release service. This service is delivered by the IT Services major AVON. The case study covers the full lifecycle of the innovation in service, from the identification of the need, conceptualization and creation of the service offering up till pilot execution. The important aspects of innovation in the revenue model and service delivery model are also covered. The case can be analyzed from two perspectives, as a detailed lifecycle of a major innovation in service or as a requirement of dynamic capabilities in the IT service provider organization, to bring about that innovation.